List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia - Aslan, Ebru Gül; Mumladze, Levan; Japoshvili, George (Zootaxa, 2017)
Leaf beetles of Lagodekhi National Park have been studied for the first time. Thirty two species were recorded from the area of which 14 are new for Georgia, 1 genus and 8 species are new to Transcaucasus. Together with the additional 16 species that were already known from literature, a total of 48 chrysomelid species for Lagodekhi reserve is listed here with notes on the specimens examined and general distributions. Some insights into the elevational pattern of leaf beetle diversity in Lagodekhi National Park are also provided.